Specificities in research of the load regimes of fast tracked vehicles - Dragan Lazarević; Zoran Popović (Vojnotehnički Glasnik, 1997)
Knowledge of the vehicle load regimes is a prerequisite for an adequate, rational and reliable construction. Research of the vehicle load regimes and vehicle transmission in general, and especially in the field of the FTV, is associated with a lot of problems that should be solved before every approach to the research. The compact construction of the FTV transmissions, with many devices and assemblies placed in a single shell, with the possibility that a circulation and a recuperation of the power within the transmission occur, make that problem even more complex.